2019
DOI: 10.1787/3388385e-en
|View full text |Cite
|
Sign up to set email alerts
|

Do digital skill certificates help new workers enter the market?

Abstract: JT03443671This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Skill certifications generate benefits to the society such as updating the skills/knowledge of the older generation, migrants, or minority groups. Nevertheless, Kässi and Lehdonvirta (2019) demonstrate that obtaining these types of certificate is a signaling device that increases earnings but does not necessarily increase productivity. Therefore, higher education systems should establish and regulate digital education schemes.…”
Section: Implications For Policymentioning
confidence: 94%
See 1 more Smart Citation
“…Skill certifications generate benefits to the society such as updating the skills/knowledge of the older generation, migrants, or minority groups. Nevertheless, Kässi and Lehdonvirta (2019) demonstrate that obtaining these types of certificate is a signaling device that increases earnings but does not necessarily increase productivity. Therefore, higher education systems should establish and regulate digital education schemes.…”
Section: Implications For Policymentioning
confidence: 94%
“…Using a unique dataset of 145 universities around the world that developed 67 percent of the MOOC courses offered during 2012 to 2017, the findings shed some light on the antecedents (ordinary capabilities) and the consequences (university outcomes) of intrapreneurial capabilities when universities adopt a MOOC orientation in the digital economy. The study enhances three academic debates in the strategic management and entrepreneurship fields: firstly, discussion about the technological and entrepreneurial transformation of universities to compete simultaneously in online and offline learning environments (Burd et al, 2015;Crossan & Apaydin, 2010;Daly, 2017;Ghemawat, 2017;Klofsten et al, 2019;Lyons, 2017;Nambisan, 2017); secondly, discussion about the role of MOOCs as important enablers, and their mediating role connecting antecedents and outcomes to generate universities' value-added in the digital economy (Aguinis et al, 2017;Eriksson, 2014); and thirdly, we provoke discussion about the role and actions of key players such as university managers, employers, and higher education authorities in the digital higher education market Urbano, 2019a, 2019b;Kässi & Lehdonvirta, 2019;OECD, 2018;Reich & Ruipérez-Valiente, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that these organisations have different motivations to enter this market. HEIs offer alternative credentials for several reasons, including increasing their visibility and reputation, experimenting with new pedagogies and technologies, generating additional income or reducing costs, as well as increasing their responsiveness to leaners' and labour markets' demands (Jansen and Schuwer, 2015 [42]).…”
Section: Content Providers' Motivation and Benefitsmentioning
confidence: 99%
“…Surveys of HEIs in Europe and the United States show that one-quarter of respondents reported that increasing the visibility of institutions is a primary objective of offering MOOCs (Allen and Seaman, 2015 [44]; Jansen and Schuwer, 2015 [42]). HEIs in both Europe and the United States also offer MOOCs in order to provide flexible learning opportunities and explore innovative pedagogy (around 15% of the respondents).…”
Section: Content Providers' Motivation and Benefitsmentioning
confidence: 99%
See 1 more Smart Citation